How Government Specific Language Favored Policies Shape Language Hierarchy in Multilingual Context: A Look Back at Nepal’s History - Sharma, Hari Maya (Gipan, 2024)
This study explores the role of government specific language favored policies in shaping language hierarchy in multilingual contexts. The study looks back at Nepal’s history illustrating governments’ activities and behavior towards two languages: Nepali and Newar as representative cases. The study was based on macro-level analysis of contents related to governments’ behavior and policies towards these two languages. It also analyzed the contents about influential individuals’ contribution to the development of those languages to show how governments’ particular language favored LPPs plays a determinant role in creating language hierarchy and positioning regardless of significant contribution of influential individuals to the development of a particular language i.e., either Nepali or Newar. The study reveals that governments’ Nepali language favored policies uplifted the status of Nepali language whereas its unfavorable policies towards the Newar language degraded its status by confining it as an ethnic language, despite it having rich literature, advanced functions and large number of native speakers in the past.